2012
DOI: 10.1351/pac-con-11-10-34
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for natural products containing chroman spiroketals

Abstract: Two cycloaddition strategies are described that lead to various chroman spiroketals from assorted exocyclic enol ethers. Unlike conventional thermodynamic ketalization strategies, the stereochemical outcome for this approach is determined by a kinetic cycloaddition reaction. Thus, the stereochemical outcome reflects the olefin geometry of the starting materials along with the orientation of the associated transition state. However, the initial kinetic product can also be equilibrated by acid catalysis and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(17 reference statements)
1
9
0
2
Order By: Relevance
“…As anticipated from our earlier work with base-promoted generation of o-QMs, 8,9 we found that when an ethereal mixture of phenol acetate 12 and enol ether 9 was treated at -78 °C with tert-butylmagnesium chloride, the spiroketal 14 was formed in 64% yield (Scheme 4). We presume this smooth reaction is due to the controlled generation of the o-QM intermediate 13 by base-mediated elimination of the acetate, and subsequent inverse demand cycloaddition with the enol ether 9.…”
Section: Scheme 4 Base-triggered O-qm Generation and Cycloadditionsupporting
confidence: 58%
“…As anticipated from our earlier work with base-promoted generation of o-QMs, 8,9 we found that when an ethereal mixture of phenol acetate 12 and enol ether 9 was treated at -78 °C with tert-butylmagnesium chloride, the spiroketal 14 was formed in 64% yield (Scheme 4). We presume this smooth reaction is due to the controlled generation of the o-QM intermediate 13 by base-mediated elimination of the acetate, and subsequent inverse demand cycloaddition with the enol ether 9.…”
Section: Scheme 4 Base-triggered O-qm Generation and Cycloadditionsupporting
confidence: 58%
“…The selective and efficient synthesis of spiroacetals has attracted much attention in the synthetic community [1][2][3][4][5][6][7][8][9] both because of the synthetic challenge of complex spiroacetal natural products, as well as the drive to develop and improve existing methods. This review aims to cover recent reports (2008 onwards) of methods for the synthesis of spiroacetals and their application in natural product synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Since the discovery of the rubromycins various synthetic approaches towards [5,6]-bisbenzannulated spiroketals have been developed. [4,7] To date only the total synthesis of the racemic aglycone of heliquinomycin by Danishefsky (2001) [8] and only two total syntheses of (AE)-g-rubromycin by Kita (2007) [9] and Pettus (2011) [10] and the total synthesis of (AE)-drubromycin by Li (2013) [11] are known. Notably, none of these total syntheses relies on an obvious acid-mediated ketalization [12] for the generation of the spiroketal core.…”
mentioning
confidence: 99%